2018
DOI: 10.1002/nme.5919
|View full text |Cite
|
Sign up to set email alerts
|

A hybridizable discontinuous Galerkin method for two‐phase flow in heterogeneous porous media

Abstract: We present a new method for simulating incompressible immiscible two-phase flow in porous media. The semi-implicit method decouples the wetting phase pressure and saturation equations. The equations are discretized using a hybridizable discontinuous Galerkin method. The proposed method is of high order, conserves global/local mass balance, and the number of globally coupled degrees of freedom is significantly reduced compared to standard interior penalty discontinuous Galerkin methods. Several numerical exampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…To the best of our knowledge, there are very few papers on HDG for complex porous media flows. Recently, we applied the HDG method to two-phase flows in [20] Examples of standard DG methods for miscible displacement can be found in [21,6]. Classical primal non-compatible DG methods that are used for the Darcy system require special attention.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there are very few papers on HDG for complex porous media flows. Recently, we applied the HDG method to two-phase flows in [20] Examples of standard DG methods for miscible displacement can be found in [21,6]. Classical primal non-compatible DG methods that are used for the Darcy system require special attention.…”
Section: Introductionmentioning
confidence: 99%
“…11 Recently, the HDG method has been applied in two-phase flow through porous media. [18][19][20] It has all the advantages of the discontinuous Galerkin formulations. This method introduces the trace of the scalar variable as a new unknown.…”
Section: Related Workmentioning
confidence: 99%
“…2,[8][9][10][11][12][13][14][15][16][17] Recently, many efforts have been focused on applying high-order methods to these kind of problems due to their advantages. 11,15,[18][19][20] If the analytical solution is smooth enough, then the numerical solution obtained with a method of order k converges to the analytical one as h k e in L 2 -norm, being h e the element size of the mesh. [21][22][23] Hence, it has been shown that high-order spatial discretization methods can be more accurate than low-order ones for the same mesh resolution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HDG simulations of immiscible incompressible two-phase flows in heterogeneous porous media were first proposed in [130] and coupled with high-order diagonally implicit Runge-Kutta (DIRK) time integrators in [107]. Moreover, in [168] a linear degenerate elliptic problem modelling two-phase mixture is approximated using a hybridised DG approach.…”
Section: Two-phase Flows and Heterogeneous Porous Mediamentioning
confidence: 99%